Juridical Analysis of Bank Indonesia Policy On E-Money Payment System During The COVID-19 Pandemic Over OVO Payment System Case Study - Dumauly Hutahayan; Hero Samudra (Journal of Multidisciplinary Academic, 2021)
Now days the development of digital-based payment systems is increasing. This progress provides many benefits and conveniences for the community, especially during the Covid-19 pandemic. The OVO payment system with Android or IOS applications that can be installed via Android Google Play store or IOS Apps Store, as part of the E-Money payment system which regulated by Bank Indonesia (BI). OVO as a payment system that consumers expect is safe, fast and efficient, it turns out that a defective transaction has occurred. In this case, the transaction was unsuccessful, but the OVO balance has been deducted, so the consumer is at a loss. This study which aimed to analysis of Bank Indonesia's Policy on the E-Money Payment System during the Covid-19 Period (Study on the OVO Payment System). The research uses a normative method, using secondary data sources in the form of legislation and a library approach as well as consumer complaints in reader’s letter in online media. The results of the research that the OVO Internal Policy in the Internal Terms and Conditions that apply to consumers is contrary to Bank Indonesia Policy in Bank Indonesia Regulation (PBI) Number 20/6/PBI/2018 concerning Electronic Money; PBI Number 22/20/PBI/2020 concerning Bank Indonesia Consumer Protection; PBI Number 18/40/PBI/2016 Concerning the Implementation of Payment Transaction Processing; PBI Number 22/23/PBI/2020 Concerning the Payment System, especially in terms of consumer protection due to a standard clause that limits OVO's responsibility for compensation in the event of a violation or mistake to the detriment of consumer. The provisions of the legislation governing consumer legal protection in the form of the obligation for payment system service issuers to have a mechanism for handling consumer complaints, regarding the principle of responsibility and legal remedies for consumers in compensation. All digital business systems use internal Terms and Conditions against their users. OVO must be responsible, if it violates the provisions of the legislation relating to consumer protection. Consumers can take legal action through legitimacy and non-legitimacy, if the obligations of OVO are not fulfilled in handling complaints for consumer losses that occur in a transaction using the OVO digital payment system. Bank Indonesia, OJK and YLKI as institutions that handle consumer complaints if the issuer of the digital or fintech payment system does not fulfil their obligations to consumers.